Employees’ performance and working environment and its connection to entrepreneurs - Kamaruddin, Kardina; Ali, Noor Malinjasari; Borhanuddin, Rahayu Izwani; Mokhlas, Hasmi (Universiti Teknologi MARA, Terengganu, 2022)
In order to be successful entrepreneurs, sometimes we cannot work alone. Sometimes, we need a helping hand to manage our business either we have mentor that could guide us into the right path or employees that are committed to their craft. In order for entrepreneurs to manage their employees well, they need to know about employees’ performance and the working environment that they will be provided.